DEFINITION OF NORMATIVE CEPHALOMETRIC PARAMETERS BY STEINER METHOD FOR UKRAINIAN YOUNG MEN AND WOMEN - Гаралов, Ф.А. (World of Medicine and Biology, 2016)
In the article the cephalometric parameters used in the analysis of Steiner for boys and girls Podilskiy region of Ukraine with orthognathic bite, assessment of sexual differences of these parameters and the comparison of the results with data obtained by C. Steiner. It is shown that the majority of cephalometric parameters derived from boys and girls with of Podillya orthognathic bite have virtually no differences with the value of these parameters obtained by C. Steiner.